Bullying in the Countryside: Prevalence, Factors and Coping Mechanism - Wong, Jonathan P.; Wong, Amaranth M. (Advances in Social Sciences Research Journal, 2017)
Bullying though old is now becoming widespread and a worldwide problem especially among schools. Incidence of bullying even in the countryside are becoming observable. The prevalence of bullying needs special attention as current literature confirm its adverse effect to both the bully and the bullied. This study was initiated primarily to determine the common bullying experiences of pupils in two central schools in the province of Romblon, Philippines that may serve as basis for an effective guidance and counseling program for bullying problems. The study is descriptive in nature employing a combination of quantitative and qualitative method using questionnaire and interview as techniques in gathering the data. A total of 187 grade VI pupils, two school heads from two central schools in the District of Romblon, Division of Romblon participated in the study. Findings revealed that the most prevalent physical bullying experienced by the respondents are: being pushed, punched and kicked. These happens more than once to 7 out of 10 pupils. The most common verbal bullying experienced by the respondents are: being insulted, spoken with bad words and being teased. These happens more than once to 6 to 8 pupils out of 10. The usual coping mechanism done by the respondents when bullied includes: telling their parents, teachers and friends. The factors associated with bullying behavior are: a)in terms of family, harsh discipline from parents; b)in terms of peer, influenced by friends; c)in terms of school, lack of policy against bullying; and d)in terms of environment, exposure to violent films and.